The Effects of Conducting a Functional Analysis on Problem Behavior in Other Settings: A Descriptive Study on Potential Interaction Effects. (September 2017) - Call, Nathan A.; Reavis, Andrea R.; Clark, Seth B.; Parks, Natalie A.; Cariveau, Tom; Muething, Colin S.
It has been suggested that reinforcing problem behavior during functional analyses (FAs) may raise ethical questions, such as resulting in an increase in problem behavior outside of FA sessions. The current translational study assessed whether conducting an FA resulted in increases in problem behavior outside of the FA setting for six participants using a nonconcurrent multiple baseline across participants design. The rate of problem behavior was measured outside the FA setting prior to and during an FA. Idiosyncratic results suggest that problem behavior outside of the FA setting may increase, decrease, or be unaffected by conducting an FA.